Prevalence of Low Back Pain among Physiotherapists Working in Clinics and Hospitals of Islamabad: Prevalence of Low Back Pain among Physiotherapists - Javed, Anam; Tariq, Saad; Jabeen, Tayyaba; Khan, Suliman; Naeem, Maria; Muhammad Khan, Haseeb; Waseem, Mehwish (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Lower back pain (LBP) is a prevailing musculoskeletal condition that affects nearly all individuals at certain point in their lives. Although the majority of individuals with LBP experience temporary pain or disability and rapidly resume normal activities regardless of treatment, a small percentage develop chronic pain and disability. Among those with long-term pain and disability, few return to normal activities after experiencing LBP for more than one year. Despite the lack of discrimination based on gender, race, or work environment, certain professionals, such as physiotherapists, are at a heightened risk of developing LBP. Objective: To determine the prevalence of lower back pain among physiotherapists working in clinics and hospitals of Islamabad. Methods: A descriptive cross-sectional study was performed using demographic data, visual analogue scale (VAS) and OSWESTRY low back disability questionnaire to determine the prevalence of lower back pain among physical therapists working in clinics and hospitals of Islamabad. The study participants were physiotherapists working in Islamabad with age between 23 to 35 years. Data were analyzed by SPSS version-25. Results: A total of 50 physiotherapists participated in the study. Results showed that out of 50 participants, 50% had moderate amount of pain following the mild pain that was 44% and 6% showed no pain measured through Visual analogue pain scale. Conclusions: The present study concludes that low back pain is prevalent among physiotherapists working in clinics and hospitals of Islamabad.